БОШЛАНҒИЧ СИНФ ЎҚУВЧИЛАРИНИНГ ЎҚУВ-БИЛУВ МОТИВАЦИЯСИНИ МУСТАҚИЛ ИШЛАР ВОСИТАСИДА ШАКЛЛАНТИРИШ – МЕТОДИК МУАММО СИФАТИДА - Турумбетова, А. (SCIENCE and SOCIETY, 2024)
The article discusses academic motivation and the motivation of primary school students in education. It is explained that the initial stage of the educational system is acquired at an early school age.
Keywords: primary class; methodology; motivation; independent work; lesson study